(untitled) (Eurasian Scientific Herald, 2022)
The research aims to study rock slope stability for the northwestern plunge of hamrin anticline fold north Iraq in (4) stations in the fatha formation. A survey of the rocky slopes was carried out, which included the engineering descriptions at each station. The study showed that the slopes in the studied stations are classified depending on the relationship of the direction of the strike slopes with the strike of layers to the type of parallel, orthogonal and oblique side types. Through the field study, it was found that the most common occurrence is rockfall, followed by toppling and then wedge sliding and that the probability to occur is rockfall, followed by toppling and then plane sliding and wedge sliding